Finding Nemo [videorecording (DVD)] - Walters, Graham; Stanton, Andrew; Unkrich, Lee; Brooks, Albert, 1947-; DeGeneres, Ellen; Gould, Alexander, 1994- (Buena Vista Home Entertainment, 2003)
The fretful Marlin and his young son Nemo become separated from each other in the Great Barrier Reef. Nemo, a clown fish, is unexpectedly taken from his home and thrust into a fish tank in a dentist's office overlooking Sydney Harbor. Buoyed by the companionship of a friendly fish named Dory, Marlin embarks on a dangerous trek and finds himself the unlikely hero.